Experimental Fiber-Based Quantum Triangle-Network Nonlocality with a Telecom AlGaAs Multiplexed Entangled-Photon Source - O. Meskine; I. Šupić; D. Markham; F. Appas; F. Boitier; M. Morassi; A. Lemaître; M.I. Amanti; F. Baboux; E. Diamanti; S. Ducci (PRX Quantum)
The exploration of the concept of nonlocality beyond standard Bell scenarios in quantum network architectures unveils fundamentally new forms of correlations that hold a strong potential for future applications of quantum communication networks. To materialize this potential, it is necessary to adapt theoretical advances to realistic configurations. Here, we consider a quantum triangle network, for which is has been shown in theory that, remarkably, quantum nonlocality without inputs can be demonstrated for sources with an arbitrarily small level of independence. We realize such correlated sources experimentally by carefully engineering the output state of a single AlGaAs multiplexed entangled-photon source, exploiting energy-matched channels cut in its broad spectrum. This simulated triangle network, based on standard fiber telecom components, is then used to violate experimentally a Bell-like inequality that we derive to capture the effect of noise in the correlations present in our system. We also rigorously validate our findings by analyzing the mutual information between the generated states. Our results allow us to deepen our understanding of network nonlocality while also pushing its practical relevance for quantum communication networks.